Enhanced performance for photocatalytic hydrogen evolution using MoS2/graphene hybrids. (29th January 2021) - Lee, Gang-Juan; Hou, Yu-Hong; Chen, Chin-Yi; Tsay, Chien-Yie; Chang, Yu-Cheng; Chen, Jing-Heng; Horng, Tzyy-Leng; Anandan, Sambandam; Wu, Jerry J.
Abstract: A MoS2 /graphene hybrid (MSG) is synthesized by microwave hydrothermal method. Both of the charge transfer resistance and the photocurrent are tuned in graphene modified MoS2 by enhancing photocatalytic nature, where the charge transfer resistance significantly decreases from 36, 000 Ω–8.49 Ω and the photocurrent promotes from 0.29 mA cm −2 to 16.47 mA cm −2 . In this article, the result reveals that the appropriate modification of graphene can reach the maximum yield of hydrogen gas. In addition, the appropriate conditions, such as the concentration of 0.32 M formic acid and the MoS2 photocatalyst with 0.8 wt% graphene (MSG0.8 ) dose of 0.013 g L −1, can complete the outstanding photocatalytic hydrogen evolution, where the hydrogen evolution using MSG0.8 composite photocatalyst has the maximum yield of 667.2 μmol h −1  g −1 . Graphical abstract: Image 1 Highlights: Graphene modified MoS2 could tune the charge transfer resistance and the photo current as well. Formic acid acts as electron donor to capture photogenerated holes to improve hydrogen production. MSG0.8 has the maximum hydrogen evolution rate of 667.2 μmol h −1  g −1 .